TECHNOLOGIES OF MODELING EDUCATIONAL MATERIALS BASED ON IMITATION-VARIATION THROUGH INDEPENDENT EDUCATION IN THE TRAINING OF FUTURE ENGINEERS (Scientific journal of the Fergana State University, 2024)
In this article, the scientific significance of modeling technologies of virtual processes on the basis of imitation-variation, as well as on the independent education of training materials on the basis of imitation-variation, is revealed. Problems of formation on the basis of related technologies and the methodology of development of pedagogical activities of the educational process are highlighted on the example of organizing independent education. This article notes that the purpose of the study is to investigate the theoretical foundations of technologies for improving student learning on an imitation-variative basis in the process of independent learning, research methods are the study of pedagogical, didactic, psychological and methodological literature, correlational, theoretical and comparative analysis, social survey (questionnaire, analytical conversation, interview, diagnostics), pedagogical observation, modelling, pedagogical experience, expert evaluation, didactic developments, questions and tasks aimed at the development of technologies to improve student learning on the imitation-variative basis in the process of independent learning based on foreign experience and innovative ideas, improvement and systematisation of issues related to modular technological education, which is explained by the development of scientific and methodological recommendations aimed at their implementation in the independent educational process.